The Effect of Moringa oleifera (Lam) Leaf Extracts on Growth of Chicken Embryo Induced by Alkohol - Indah Kusuma Wardani; Suryono Suryono (NurseLine Journal, 2019)
Fetal Alcohol Syndrome (FAS) is a condition associated with drinking alcohol during pregnancy and affect embryo development. FAS is the most common congenital disabilities in the world. The effects of FAS are mental retardation, cranial abnormalities, and heart defects. Moringa oleifera is a highly valued plant. It has an impressive range of biological activities, including antioxidant, antiproliferation, and anti-inflammatory. This study aims to assess the effect of Moringa oleifera leaf extracts in inhibiting growth retardation of chicken embryo growth induced by alcohol. The study was a true experimental design with posttest controlled group design. There were five groups with 5 of chicken embryo each group. The treatments contained 15% alcohol and aquadest as positive control (P+), without alcohol as negative control (P-), P0.5 (0,5g/dl), P5 (5g/dl), P50 (50g/dl) by adding Moringa oleifera leaf extracts, respectively. Moringa oleifera leaf extracts showed the improvement of length and head diameter as a benchmark for chicken embryo development with P5 concentration showed the best results to overcome growth retardation in alcohol-induced chicken embryos. This finding implies against possibility Moringa oleifera leaf extracts can be alternative medicine to prevent growth retardation.